Impact of corporate social responsibility on organizational performance with reference to selected banks in india-reviews and conceptual frame work - Praveen kumar, T.; Priyadharshini, K. (university of Jaffna, 2014)
Indian business, which is today viewed globally as a responsible component of the ascendancy of India, is poised now to take on a leadership role in the challenges of our times. It is recognized the world over that integrating social, environmental and ethical responsibilities into the governance of businesses ensures their long term success, competitiveness and sustainability. This literature review has aimed at providing more than just an enumeration of extant publications. By suggesting a conceptual framework (figure1) to structure the different concepts used in literature we hope to advance towards a better understanding of the CSR and its impact.
Keywords: Corporate social responsibility & organizational performance